Dinamika Work Life Balance pada Karyawan: Menjaga Keseimbangan Kehidupan Kerja dan Pribadi di Tengah Tuntutan Kerja - Dzakiyyah Hasna Aziza; Christian Wiradendi Wolor (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the condition, efforts, and factors influencing employees’ Work-Life Balance (WLB) at an e-commerce company amid increasing job demands. Adopting a qualitative approach with a descriptive case study design, empirical data were collected from March to June 2026 through participant observation, in-depth interviews, and a comprehensive literature review. Informants were selected using purposive sampling and consisted of one senior staff member and two staff members. Data were analyzed using the interactive model of Miles and Huberman, while data validity was ensured through source and method triangulation. The findings indicate that the employees’ Work-Life Balance at the e-commerce company is generally at a fairly good level, as employees are able to balance their professional and personal roles despite occasional disruptions caused by urgent work demands or increased workloads. Employees actively maintain this balance by prioritizing tasks, limiting work involvement outside working hours, and utilizing their leisure time for physical and mental recovery with their families. The main factors influencing the achievement of Work-Life Balance include individuals’ time management abilities, fluctuating job demands, emotional support from the family environment, and effective communication among colleagues within the company.